2002
DOI: 10.1046/j.0966-0410.2001.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Going home from hospital - an appreciative inquiry study

Abstract: This paper reports on a project that involved a number of agencies and groups, including older people, working together to examine and develop practice in an area of shared concern -- going home from hospital. The project was stimulated by a 'whole-system event', and was based on appreciative inquiry (AI) methodology, which has roots in both action research and organisational development. In AI, the research is directed towards appreciating what it is about the social world that is positive, and exploring this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 5 publications
0
85
0
1
Order By: Relevance
“…The focus on positive rather than negative and critical analysis, created a framework which provided fresh thinking and stimulus for dealing with the expected and the inevitable problems encountered. In fact, discussing strengths rather than problems seemed to minimize resistance, thus rendering an easier dialogue among members of teams (Reed et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus on positive rather than negative and critical analysis, created a framework which provided fresh thinking and stimulus for dealing with the expected and the inevitable problems encountered. In fact, discussing strengths rather than problems seemed to minimize resistance, thus rendering an easier dialogue among members of teams (Reed et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to bring about a change is, in fact, often only mediated by considering the different roles and power bases in organizations (Reed et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers responsible for this process (Reed et al 2002) reported that most of the participants were pleased with the appreciative inquiry process to which they had contributed. They pointed out, though, some of its limitations, including the perception that it ignored problems (by focusing on the positives), the challenges to the evaluation of the process and the fact that (on this occasion) the quality of the action plans was adversely affected owing to the limited participation in the process by high-level decision makers.…”
Section: Who Did the Integration And How Was It Undertaken?mentioning
confidence: 99%
“…Appreciative inquiry was used to bring together people from 37 agencies who were concerned about this problem (Reed et al 2002). It involved clarifying agency personnel visions for better hospital discharge experiences for older people and developing action plans to help turn these visions into reality.…”
Section: What Was the Integration Aiming To Achieve And Who Was Intenmentioning
confidence: 99%
See 1 more Smart Citation